The Tissue Systems Pathology Test Outperforms Pathology Review in Risk Stratifying Patients With Low-Grade Dysplasia - Khoshiwal, Amir M.; Frei, Nicola F.; Pouw, Roos E.; Goldblum, John; Montgomery, Elizabeth; Davison, Jon; Singh, Jagjit; Szymanski, Jared; Perry, Anthony; Seldenrijk, Kees; Kate, Fiebo ten; Offerhaus, G. Johan A.; et al. (Gastroenterology, 2023)
Background & Aims: Low-grade dysplasia (LGD) is associated with an increased risk of progression in Barrett's esophagus (BE); however, the diagnosis of LGD is limited by substantial interobserver variability. Multiple studies have shown that an objective tissue systems pathology test (TissueCypher Barrett's Esophagus Test, TSP-9), can effectively predict neoplastic progression in patients with BE. This study aimed to compare the risk stratification performance of the TSP-9 test vs benchmarks of generalist and expert pathology. Methods: A blinded cohort study was conducted in the screening cohort of a randomized controlled trial of patients with BE with community-based LGD. Biopsies from the first endoscopy with LGD were assessed by the TSP-9 test and independently reviewed by 30 pathologists from 5 countries per standard practice. The accuracy of the test and the diagnoses in predicting high-grade dysplasia (HGD) and esophageal adenocarcinoma (EAC) were compared. Results: A total of 154 patients with BE (122 men), mean age 60.9 ± 9.8 years were studied. Twenty-four patients progressed to HGD/EAC within 5 years (median time of 1.7 years) and 130 did not progress to HGD/EAC within 5 years (median 7.8 years follow-up). The TSP-9 test demonstrated higher sensitivity (71% vs mean 63%, range 33%–88% across 30 pathologists), than the pathology review in detecting patients who progressed (P = .01186). Conclusions: The TSP-9 test outperformed the pathologists in risk stratifying patients with BE with LGD. Care guided by the test can provide an effective solution to variable pathology review of LGD, improving health outcomes by upstaging care to therapeutic intervention for patients at high risk for progression, while reducing unnecessary interventions in low-risk patients.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Barrett's Esophagus; Esophageal Adenocarcinoma; High-Grade Dysplasia; Tissue Systems Pathology test (TSP-9); TissueCypher